2016
DOI: 10.1149/2.0391701jes
|View full text |Cite
|
Sign up to set email alerts
|

Review—On the Mechanism of Quasi-Solid-State Lithiation of Sulfur Encapsulated in Microporous Carbons: Is the Existence of Small Sulfur Molecules Necessary?

Abstract: In this work we analyzed the phenomenon of quasi solid state (QSS) lithiation of sulfur-carbon (S/C) composite electrodes with sulfur confined in the micropores of carbon matrices based on our recent studies and data published in literature. We demonstrated that the existence of sulfur in the form of small molecules is not a necessary condition for the realization of QSS mechanism. QSS operation behavior was demonstrated both for carbons with small up to 1nm micropores and for carbons with larger pore size up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
105
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(111 citation statements)
references
References 72 publications
(192 reference statements)
4
105
2
Order By: Relevance
“…Microporous structure plays an important role in the formation of small sulfur molecules. To confine the sulfur, a variety of microporous carbon hosts have been developed, such as nitrogen-doped microporous carbon, subnanometer 2D graphene, microporous structure carbon nanotubes, and pyrolyzed polymer derived carbon [140][141][142]. Lou et al [134] employed novel metal-organic-framework (MOF), ZIF-8, to develop a microporous carbon host for sulfur cathodes.…”
Section: A Confined Sulfur Molecules In Microporous Structuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Microporous structure plays an important role in the formation of small sulfur molecules. To confine the sulfur, a variety of microporous carbon hosts have been developed, such as nitrogen-doped microporous carbon, subnanometer 2D graphene, microporous structure carbon nanotubes, and pyrolyzed polymer derived carbon [140][141][142]. Lou et al [134] employed novel metal-organic-framework (MOF), ZIF-8, to develop a microporous carbon host for sulfur cathodes.…”
Section: A Confined Sulfur Molecules In Microporous Structuresmentioning
confidence: 99%
“…Further, there are many challenges and unrevealed electrochemical mechanisms related to the use of small sulfur molecule. One review paper published by Aurbach et al [142] raised questions on the mechanism of small sulfur molecules and stated that they are not the only way to make functionalized sulfur cathodes in carbonate electrolyte. The author proposed that the SEI layer formation on the cathode during the initial charging process played a key role in quasi-solid-state Li-S reactions.…”
Section: A Confined Sulfur Molecules In Microporous Structuresmentioning
confidence: 99%
“…[105] Among them, the latter approach is favored by most researchers. [105] Among them, the latter approach is favored by most researchers.…”
Section: Carbonate-based Electrolyte With a Short-chain Sulfur-based mentioning
confidence: 99%
“…Very recently, Aurbach and co-workers [105] claimed that porous carbon, with a pore size of 2-3 nm, can not only accommodate short-chain sulfur but can also accommodate long-chain sulfur or octasulfur (S 5 to S 8 ) and also exhibits the same discharge plateau behavior, which invalidates the proposed effect of the confinement of small-chain sulfurs in the microporous carbon. Very recently, Aurbach and co-workers [105] claimed that porous carbon, with a pore size of 2-3 nm, can not only accommodate short-chain sulfur but can also accommodate long-chain sulfur or octasulfur (S 5 to S 8 ) and also exhibits the same discharge plateau behavior, which invalidates the proposed effect of the confinement of small-chain sulfurs in the microporous carbon.…”
Section: Carbonate-based Electrolyte With a Short-chain Sulfur-based mentioning
confidence: 99%
“…A solid-solid mechanism of lithiation/delithiation reactions of the small S2-4 molecules was suggested [21], although it has been recently reported that small S molecules in the micropores of carbon matrices is not a necessary condition such that this mechanism is realized. [22] Microporous carbon were either obtained by means of templating [23] or by pyrolysis of biomass [24] but Ryu et al [25] had shown that it is possible to achieve high capacity sulphur cathode using solution impregnation only. Others reported ball mixing, melt infusion, and vapour phase diffusion to achieve homogenous impregnation of sulphur into the pores [5,8,10].…”
Section: Introductionmentioning
confidence: 99%